PENGARUH KOMUNIKASI TERAPEUTIK YANG EFEKTIF TERHADAP KECEMASAN PASIEN DI IGD RS LAVALETTE MALANG - Wahyu Handrianto; Nurul Mawaddah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Emergency room (ER) have assignments of administering medical services and nursing care as well as emergency surgery services for patients who visit with the medical emergency. Measures taken in times of emergency should be completely effective and efficient. This emergency disorder causes patients to develop an unstable psychological disorder of excessive fear, a sense of despairing and anxiety. Stress and anxiety conditions can be lowered by therapeutic communication. The purpose of this study was to understand the effect effective therapeutic communication has on the patients' anxiety at ER Lavalette hospital. . The research design is a pre-test post-test design with consecutive sampling technique and the number of samples is 32 respondents. The interventions conducted in the study was doing the therapeutic communication against anxiety rates of patients in ER. The result showed before being given effective therapeutic communication, respondents were mild anxiety 40.6%, moderate anxiety 53.1%, and severe anxiety 6.3%. After being given effective therapeutic communication, respondents were no anxiety 59.4%, mild anxiety 37.5%, and moderate anxiety 3.1%. Based on the statistical analysis of Wilcoxon signed ranks, p-value = 0.000 was obtained with a significance level of <0.05. The results of this research can be used as a reference for effective therapeutic communication techniques in emergency conditions in the ER. The conclusion of this study there was impact of effective therapeutic communication on patients anxiety in the ER.